2008
DOI: 10.1093/annonc/mdm486
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of changes between 2-year disease-free survival and 5-year overall survival in adjuvant breast cancer trials from 1966 to 2006

Abstract: There is a statistically significant correlation, of moderate strength, between difference in 2-year DFS between treatment comparisons and difference in 5-year OS but the correlation is not strong enough to be used as a predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…In a 2007 meta-analysis of 10 randomized clinical trials of AIS versus tamoxifen, a strong correlation between DFS and OS was found 17, supporting the use of DFS as a surrogate endpoint for OS in breast cancer adjuvant endocrine trials. Further support was demonstrated in a recent analysis of 128 breast cancer adjuvant trials in which the difference in 2-year DFS was found to be a significant predictor of the difference in 5-year OS 18.…”
Section: Trial Endpointsmentioning
confidence: 80%
“…In a 2007 meta-analysis of 10 randomized clinical trials of AIS versus tamoxifen, a strong correlation between DFS and OS was found 17, supporting the use of DFS as a surrogate endpoint for OS in breast cancer adjuvant endocrine trials. Further support was demonstrated in a recent analysis of 128 breast cancer adjuvant trials in which the difference in 2-year DFS was found to be a significant predictor of the difference in 5-year OS 18.…”
Section: Trial Endpointsmentioning
confidence: 80%
“…Several meta-analyses have been published (Table 1) that show a link between time-toprogression (TTP) or progression-free survival (PFS) with overall survival (OS) in metastatic colorectal or non-small cell lung cancer (Johnson et al, 2006) and colon cancer in the adjuvant setting (Sargent et al, 2005). For breast cancer, a moderately strong correlation between 2-year disease-free survival and 5-year overall survival was observed in the adjuvant setting (Ng et al, 2008). A meta-analysis of metastatic breast cancer studies found a positive relationship between objective response and overall survival on an individual patient basis, but the relationship was less clear when treatment regimens were compared (Bruzzi et al, 2005).…”
mentioning
confidence: 99%
“…Follow-up in our study was not long enough to assess patient prognosis (two years). Indeed, Ng et al reported that, despite the existence of a correlation between 2-year PFS and 5-year overall survival, the correlation was not strong enough to be used as a predictor [22]. …”
Section: Discussionmentioning
confidence: 99%